Anioły są wśród nas. Studium pism św. Paulina z Noli - Wysocki, Marcin (Vox Patrum, 2023)
Paulinus of Nola (c. 355-431) is undoubtedly one of the most interesting yet least known figures of early Christianity. Born into a wealthy senatorial family from Bordeaux, Paulinus gave up wealth, a career as a civil servant and the practice of secular poetry to follow St Felix on the path of Christian faith. One of its elements was the belief in the existence of angels. In the case of Paulinus of Nola, this belief took on a very concrete expression. The aim of this article is to show, on the basis of an analysis of the surviving letters and songs, the angelology of St Paulinus, which took on above all a pastoral aspect and showed very concrete manifestations of the action of angels for the benefit of the human beings.